#### Answer

Input: -5
Output: 3

#### Work Step by Step

We substitute x = -5 into the function.
$-\frac{2(-5)+1}{3}=-\frac{-10+1}{3}=-\frac{-9}{3}=-(-3)=3$

Published by
Prentice Hall

ISBN 10:
0133186024

ISBN 13:
978-0-13318-602-4

Input: -5
Output: 3

We substitute x = -5 into the function.
$-\frac{2(-5)+1}{3}=-\frac{-10+1}{3}=-\frac{-9}{3}=-(-3)=3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.